Analysis of Lack of Basis for Judge Considerations in Cases of Abortion by Teenagers - LM Ady Saputra (Universitas Negeri Gorontalo, 2022)
The purpose of this writing is to analyze what the judges consider about the crime of abortion (Decision Study Number: 90/Pid.Sus/2021/PN/Gto). The writing method used is Normative writing, using 2 approaches namely; law (statute approach) and a case approach (case approach). The results of this writing show; In decision Number: 90/Pid.Sus/2021/PN/Gto. Judges are not based on strong juridical considerations by applying the principle of lex specialist derogate legi general and the principle of lex posterior derogate legi priori,